2022
DOI: 10.3389/fgene.2022.854993
|View full text |Cite
|
Sign up to set email alerts
|

Construction and Bioinformatics Analysis of circRNA-miRNA-mRNA Network in Acute Myocardial Infarction

Abstract: Background: Acute myocardial infarction (AMI) is one of the main fatal diseases of cardiovascular diseases. Circular RNA (circRNA) is a non-coding RNA (ncRNA), which plays a role in cardiovascular disease as a competitive endogenous RNA (ceRNA). However, their role in AMI has not been fully clarified. This study aims to explore the mechanism of circRNA-related ceRNA network in AMI, and to identify the corresponding immune infiltration characteristics.Materials and Methods: The circRNA (GSE160717), miRNA (GSE24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…et al for AMI suggested that the hsa_circ_0009018/hsa-miR-139-3p/BCL6 axis was significantly positively correlated with upregulated immune cells in AMI, which may be represent potential therapeutic targets (47). All of these data suggest the importance of BCL6 in cardiovascular disease or senescence.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…et al for AMI suggested that the hsa_circ_0009018/hsa-miR-139-3p/BCL6 axis was significantly positively correlated with upregulated immune cells in AMI, which may be represent potential therapeutic targets (47). All of these data suggest the importance of BCL6 in cardiovascular disease or senescence.…”
Section: Discussionmentioning
confidence: 91%
“…Moreover, Altieri et al found that BCL6 cooperates with PPARdelta to protect the heart from doxorubicin-induced senescence ( 46 ). Using bioinformatics, the circRNA-miRNA-mRNA network constructed by Zhou et al for AMI suggested that the hsa_circ_0009018/hsa-miR-139-3p/BCL6 axis was significantly positively correlated with upregulated immune cells in AMI, which may be represent potential therapeutic targets ( 47 ). All of these data suggest the importance of BCL6 in cardiovascular disease or senescence.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we found that the myocardial infarction group contained higher proportions of macrophages (P<0.01), mast cells (P<0.01), monocytes (P<0.01), and neutrophils (P<0.01). Jin Zhou similarly found a trend of upregulation of neutrophils and macrophages in patients with myocardial infarction [25] . Zhang X showed a trend of upregulation of neutrophils and macrophages by established a myocardial infarction model by ligating the anterior descending branch of the left coronary artery in Syrian hamsters and found that the number of mast cells was much higher in the myocardial infarction group than in the control group [26] .…”
Section: Discussionmentioning
confidence: 90%
“…Furthermore, evidence of the role of circRNA-modulated miRNAs has been reported using in vitro hypoxia/reperfusion models as well as in vivo [ 191 , 192 ]. In an in vitro model of hypoxia/reperfusion, the administration of exosomes with high amounts of circ_0001747 partially recovered CM dysfunction by targeting the miR-199b/MCL1 (induced myeloid leukemia cell differentiation protein) signaling pathway.…”
Section: The Emerging Impact Of Non-coding Rnas’ Regulation Of Cardia...mentioning
confidence: 99%
“…In an in vitro model of hypoxia/reperfusion, the administration of exosomes with high amounts of circ_0001747 partially recovered CM dysfunction by targeting the miR-199b/MCL1 (induced myeloid leukemia cell differentiation protein) signaling pathway. Exosomes with high levels of circ_0001747 attenuate in vitro hypoxia/reperfusion-induced HL-1 dysfunction partly by targeting miR-199b-3p/MCL1 signaling [ 191 ]. Similarly, lncRNA-modulated miRNAs are also important in this context.…”
Section: The Emerging Impact Of Non-coding Rnas’ Regulation Of Cardia...mentioning
confidence: 99%